2005
DOI: 10.1111/j.1745-7262.2005.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of long-term vas occlusion with styrene maleic anhydride and its non-invasive reversal on accessory reproductive organs in langurs

Abstract: SMA vas occlusion and its non-invasive reversal do not damage the accessory reproductive organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…inside the vas tube (Guha et al, 1985;Guha, 2007).The contraceptive has been proved to be safe (Manivannan et al, 2005), antimicrobial (Sharma et al, 2003;Guha, 2005), long-term effective (Chaudhury et al, 2002;Jha et al, 2009a) and reversible (Lohiya et al, 2000). Non-invasive reversibility of SMA analogues under guidance of electromagnetic field is also possible (Jha et al, 2009b).…”
Section: Discussionmentioning
confidence: 97%
“…inside the vas tube (Guha et al, 1985;Guha, 2007).The contraceptive has been proved to be safe (Manivannan et al, 2005), antimicrobial (Sharma et al, 2003;Guha, 2005), long-term effective (Chaudhury et al, 2002;Jha et al, 2009a) and reversible (Lohiya et al, 2000). Non-invasive reversibility of SMA analogues under guidance of electromagnetic field is also possible (Jha et al, 2009b).…”
Section: Discussionmentioning
confidence: 97%
“…It has been tested in animals and men for safety and reversibility [62,63]. Although an earlier report questioned the likelihood of reversibility, after using the procedure for long periods of time [57], recent studies have demonstrated that the testes and vas deferens of the treated animals gradually return to normal 5 months after reversal [62,64].…”
Section: Surgical and Non-surgical Vas Deferens-based Approaches To Rmentioning
confidence: 96%
“…Le gel tapisse la paroi interne et se solidifie en quelques minutes ; lorsque les spermatozoïdes passent dans le canal au moment de l'éjaculation, ils entrent en contact avec la surface du polymère, dont la combinaison en charges positives et négatives induit des perforations de la membrane des spermatozoïdes [38], ce qui leur fait perdre leur capacité à être mobiles, et ainsi leur capacité à féconder l'ovocyte. Les marqueurs chimiques de la prostate, même après 8 ans d'utilisation, ne sont pas perturbés [39], de même pour les autres glandes accessoires [40].…”
Section: Risugunclassified